MORPHOLOGICAL AND BIOCHEMICAL RESPONSES OF Amaranthus viridis TO CHEMICAL FERTILIZER AND BLACK SOLDIER FLY FRASS - Teo, Shao-Zhen; Ridzuan, Raihana; Abd Manan, Fazilah (Chilean Journal of Agricultural & Animal Sciences, 2025)
The prolonged use of chemical fertilizer is associated with adverse environmental effects. To date, insect-derived fertilizer from Black Soldier Fly (BSF), has emerged as a promising organic alternative. However, the impact of BSF frass on the morphology and biochemical compositions of leafy vegetables necessitates further investigation. Therefore, the objective of this study was to evaluate the effects of chemical NPK fertilizer and BSF frass fertilizer, applied individually or in combination, on the morphology and biochemical composition of Amaranthus viridis (A. viridis). The experiment consisted of four treatments; untreated control (T1), BSF frass (T2), NPK fertilizer (T3), and BSF frass + NPK fertilizer (T4). The results indicated that A. viridis plants in T4 exhibited the highest stem length, root length, leaf area, as well as weight of the stems, leaves, and roots. However, no significant differences were observed in terms of plant morphology and total chlorophyll content among the fertilizer treatments. Additionally, T4 significantly increased the total phenolic content in A.viridis (0.481 ± 0.012 mg GAE/g DW) compared to plants treated solely with NPK fertilizer. These results indicate that the combined application of BSF frass and NPK fertilizer significantly enhances plant growth of leafy vegetables, particularly by influencing specific biochemical compositions.